Association of follicular fluid volume with membrane stretchability of human metaphase II oocytes following the gonadotropin‐releasing hormone agonist protocol during intracytoplasmic sperm injection. (11th May 2018) - Inoue, Taketo; Taguchi, Sayumi; Hirao, Kayoko; Tsujimoto, Yoshiko; Yamamoto, Shuji; Uemura, Mikiko; Miyazaki, Kazunori; Yamashita, Yoshiki
Abstract: Purpose: The authors previously revealed the association of the follicular fluid (FF) volume with oolemma stretchability following the gonadotropin‐releasing hormone (GnRH) antagonist protocol during intracytoplasmic sperm injection (ICSI). However, the impact of the GnRH agonist protocol on oolemma stretchability remains unclear. Methods: Data that were obtained from 74 ICSI cycles were reviewed retrospectively. Controlled ovarian stimulation was performed in accordance with the short GnRH agonist protocol. Each follicle was individually aspirated and assigned to one of six groups, according to the FF volume. The oolemma stretchability during ICSI was evaluated by using a mechanical stimulus for oolemma penetration; that is, oolemma penetration with or without aspiration (high vs low stretchability, respectively). Results: The incidence of low oolemma stretchability was significantly higher in the <1.0 mL group than that in the ≥1.0 mL group. The normal fertilization rate was significantly lower in the <1.0 mL group than that in the 2.0‐<3.0 mL group. The rate of blastocyst development was lower in the <1.0 mL group than that in the 3.0‐<4.0 mL group. Conclusion: The FF volume potentially was associated with metaphase II oolemma stretchability, fertilization, and blastocyst development. Abstract : This study investigates the relationship between the follicular fluid (FF) volume aspirated from individual follicles and oocyte retrieval, oocyte maturity, oolemma stretchability, fertilization, and embryonic development following administration of a short gonadotropin‐releasing hormone (GnRH) agonist protocol. We found that the incidence of low oolemma stretchability was significantly higher in the <1.0 mL group than in the ≥1.0 mL groups. The manuscript describes the study in detail and concludes that FF volume was associated with oolemma stretchability.